2008
DOI: 10.1073/pnas.0809634105
|View full text |Cite
|
Sign up to set email alerts
|

The crystal structure of mouse VDAC1 at 2.3 Å resolution reveals mechanistic insights into metabolite gating

Abstract: The voltage-dependent anion channel (VDAC) constitutes the major pathway for the entry and exit of metabolites across the outer membrane of the mitochondria and can serve as a scaffold for molecules that modulate the organelle. We report the crystal structure of a ␤-barrel eukaryotic membrane protein, the murine VDAC1 (mVDAC1) at 2.3 Å resolution, revealing a high-resolution image of its architecture formed by 19 ␤-strands. Unlike the recent NMR structure of human VDAC1, the position of the voltagesensing N-te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

48
755
2
7

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 509 publications
(821 citation statements)
references
References 46 publications
48
755
2
7
Order By: Relevance
“…The N-terminal end of VDAC contains amphipathic a-helix elements [19]. This structure represents an addition to the b-barrel pore structure and was proposed to have functionally relevant properties [20][21][22][23][24][25][26]35].…”
Section: Role Of the Vdac N-terminusmentioning
confidence: 99%
“…The N-terminal end of VDAC contains amphipathic a-helix elements [19]. This structure represents an addition to the b-barrel pore structure and was proposed to have functionally relevant properties [20][21][22][23][24][25][26]35].…”
Section: Role Of the Vdac N-terminusmentioning
confidence: 99%
“…VDAC1 structure and FLAG-epitope positions. (A) Three-dimensional model of hsVDAC1 drawn with Pymol [DeLano Scientific] using PDB coordinates 2K4T from [11] (see also 2JK4 [12] and 3EMN [13]) indicating FLAG-epitope locations used in the current study (1)(2)(3)(4)(5). FLAG3, which contradicts the structure, is highlighted (Ã).…”
Section: Localization Of Flag-tagged Vdac1mentioning
confidence: 99%
“…The remaining epitopes reported in the only other study of orientation in intact mitochondria [20] are shown by the recent structures to be mostly buried in membrane strands and therefore difficult to interpret. In the published structures [11][12][13] the N-terminal segment first exits the membrane on the trans side [11,12] before folding through the lumen to almost reach the cis side [13]. The FLAG1, which is 11-20 residues from the N-terminus, will most likely have a trans exposure (see Fig.…”
Section: Immunoprecipitation Of Intact and Disrupted Mitochondriamentioning
confidence: 99%
See 2 more Smart Citations